The Potentials of Urban Rail Transport Development in Ibadan, Nigeria (2014)
The goal of efficient transportation in cities requires that all modes should function at their optimal capacities to provide adequate choices for commuters. However, the neglect of the rail transport has been a contributory factor to the persistent mobility crisis prevalent in Nigerian cities. Ibadan once enjoyed intra-urban rail transport services (passenger and freight) until it became moribund. Given the current rate of urban expansion and increased commuting distances within the city, this study investigated the potentials of urban rail transport development as a solution for the urban mobility crisis in Ibadan. The Spatial Interaction Theory and the Public-Private Partnership model provided the conceptual framework. Using a cross-sectional research survey, data were collected from both primary and secondary sources. The Bureau of Public Enterprises provided information on the concessioning procedure for rail transportation in Nigeria. The city was stratified into five major traffic corridors on which a seven-day traffic count was conducted to collect data on commuter threshold capacity. Salter‟s corridor sampling technique was employed in the administration of questionnaire to 642 household heads based on income groups, along the stratified traffic corridors. Data on trip pattern, trip purpose, modal choice, rail potentials, train ride and the desire for the return of intra-urban rail transport; traffic congestion reduction, commuter‟s savings from the use of rail and employment creation were collected. Analysis of variance, multinomial logit and multiple regression models were used in data analysis at p≤0.05. Only 45.5 percent of residents had previously used train as mode of transportation. The threshold capacity for urban rail commuting along the traffic corridors of Podo/Akobo (2135), Lagos Road Toll/Moniya (1610), Bere/Akanran (1542) and Mokola/Ife Road Toll (1214) exceeded the required 1200 threshold capacity. Commuting distance varied from below 5 kilometres (53%) to 35 kilometres (4.8%) within the metropolis. Trips undertaken were mainly to work places (55.6%), shops/markets (26.8%), schools (6.7%), social/multipurpose trips (12.9%). There were significant differences in trips undertaken by the high, medium and low income groups (F= 38.503). Modal choice was significantly affected by auto-ownership, trip by bus, and respondents‟ income (r=0.24). The potential use of the rail transport was a function of occupation, estimated income and trip distance of commuters (R2=0.84). Eighty-four percent of the respondents desired the return of intra-urban rail transport. Perceived potentials of rail transport included reduction in traffic congestion (84.2%), per capita traffic crash rates (76.8%), increased modal choice (68.2%), enhanced commuter savings (57.5%) and employment creation (52.7%). The traffic congestion reduction potential of the rail was high (R2=0.59). Vertical integration approach of Bureau of Public Enterprises in rail concessioning was found to attract prospective private partnership. Intra urban rail transport in Ibadan has very high potentials. There is the need to revitalise intra urban rail transport in the city through public-private partnership.